Peningkatan pengetahuan masyarakat tentang akibat pernikahan dini dari aspek kesehatan, hukum dan pendidikan di Desa Pulau Jambu Kecamatan Kuok Kabupaten Kampar - Wan Nishfa Dewi; Hayatul Ismi; Ihda Hasbiyati; Maimunah Maimunah; Ulfia Hasanah; Mukhlis Ridwan; Deviona Deviona (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Underage marriages are marriages that occur where a man or woman who has not reached the age required by applicable law, that is, if the male has reached the age of 19 and the woman has reached the age of 16. The purpose of community service activities is to provide socialization and understanding to the public about the impact of early marriage in terms of legal, health and education aspects. This activity can also improve knowledge competence, skills, community motivation, and play a role in the formation of a prosperous family village development team. Data collection techniques carried out by interview, observation and document analysis. The results of this community service show the enthusiasm of the community to attend a series of activities, and the active role of the community is quite good. Improved understanding of the community is divided into 3 categories, namely, the village prosperous village development team, health development and Education development. Activities carried out continuously and continuously have a positive impact on community growth and development.